Principles of Child Character Education Based on Qur’anic Stories: A Thematic Tafsir Tarbawi Study - Muin, M. Tamsil (Mauriduna : Journal of Islamic Studies, 2026)
The moral crisis among the younger generation marked by increasing violence, dishonesty, and the weakening of spirituality highlights the urgency of formulating a character education model rooted in the transcendental values of the Qur’an. This study aimed to identify and analyze the moral values contained in the Qur’anic educational narratives and to formulate foundational principles for character education. Employing a qualitative library research approach, this study examined classical and contemporary tafsir works as well as international scholarly articles through a thematic synthesis method. The findings revealed that Qur’anic narratives demontrated a consistent pedagogical structure that was formulated into five core principles of children’s character education, namely: (1) strengthening spiritual identity, (2) the habituation of ethical behavior, (3) reflective dialogue, (4) emotional guidance, and (5) role modeling (uswah). These five principles were found to be aligned with modern moral education theories, including Lickona’s character education framework, the Social Emotional Learning (SEL) approach, and Kohlberg’s theory of moral development. The integration of Qur’anic values with contemporary theories resulted in a holistic and applicable pedagogical model for children’s character education. The novelty of this study lay in its thematic application of tafsir tarbawi across multiple Qur’anic narratives, the formulation of synthesized Qur’anic–contemporary principles, and the development of a theoretical framework for utilizing Qur’anic stories as a systematic character education curriculum. Practically, the findings provided implications for national education policy in strengthening religious-based character education and offered conceptual references for the development of Islamic education curricula and children’s moral development programs.